2020
DOI: 10.1097/cin.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Application as a Learning Aid for Nurses and Nursing Students to Identify and Care for Stroke Patients

Abstract: Cerebrovascular accident is a serious public health problem and requires the attention of professionals who can detect, diagnose, and provide care in a timely fashion. A quantitative quasi-experimental study was conducted using a mobile app called mSmartAVC for clinical evaluation of nursing care at the bedside. The study aimed at measuring the knowledge of nurses and nursing students in the detection and care of cerebrovascular accident. In this study, a total of 115 nurses from health services in the South o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 15 publications
0
18
0
16
Order By: Relevance
“…Recently, mobile health (mHealth) using smartphones for psychotherapy has been attracting attention as useful for the upcoming post-corona era [ 46 ]. Mobile applications can be useful resources for problem solving, and providing real-time information and stress reduction strategies for nurses in a variety of healthcare fields and settings [ 47 ]. In addition, since previous studies found smartphone app-based resilience interventions effective for resilience, emotional regulation, and psychological health promotion, the development of a smartphone app-based nurse resilience enhancement program can be expected based on the results of this study [ 48 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mobile health (mHealth) using smartphones for psychotherapy has been attracting attention as useful for the upcoming post-corona era [ 46 ]. Mobile applications can be useful resources for problem solving, and providing real-time information and stress reduction strategies for nurses in a variety of healthcare fields and settings [ 47 ]. In addition, since previous studies found smartphone app-based resilience interventions effective for resilience, emotional regulation, and psychological health promotion, the development of a smartphone app-based nurse resilience enhancement program can be expected based on the results of this study [ 48 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students should use digital technologies as a way to learn the theoretical and practical part of their nursing curriculum. In the other hand, the challenges facing undergraduate nurse teaching during the current coronavirus pandemic include shifting to a completely virtual approach to theoretical teaching and learning [6][7][8][9]. knowing the best technologies and expectations of the nursing students when faced with virtual education by technologies, is necessary for helping the education and teaching authorities to assign enough resources and re-orient university education for nursing students [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] The use of mobile devices for academic and learning purpose in health-care professional education has increased in recent years and has been positively received among health-care professional students. [ 13 14 15 ] Capabilities and potentials of mobile technology can facilitate learning process in medical sciences students. Using educational applications about diseases, physical examination, drugs, audio and video clips about medical sciences, medical simulations, different educational and therapeutic games, preparing medical slides, developing medical e-books, saving and retrieving educational materials, membership in social media groups about medical sciences, and the like can have a profound effect on learning in medical sciences students.…”
Section: Introductionmentioning
confidence: 99%